2011
DOI: 10.1007/s10266-011-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries experience in relation to salivary findings and molecular identification of S. mutans and S. sobrinus in subjects with Down syndrome

Abstract: This study investigated the association between clinical and salivary or molecular parameters in Down syndrome subjects. Sixty individuals (1- to 48-year old) were clinically examined using DMFT/DMFS. Stimulated saliva was collected; salivary flow was calculated (mL/min), buffering capacity was measured using a standard pH tape. In addition, 25 μL of saliva was diluted using 10-fold-dilution method and then placed on Mitis-Salivarius-Bacitracin agar to count colony forming units (CFU/mL) of mutans streptococci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
3
9
0
3
Order By: Relevance
“…mutans and S. sobrinus are the most commonly isolated bacterial species associated with dental caries and are regarded as the main pathogenic microorganisms of the disease (10,11,14,15). The present findings show that the prevalence of mutans streptococci was 94.5% in subjects aged 11-36 years, which is consistent with the findings of a previous study of Down syndrome patients aged 1-48 years (29). However, other studies have reported lower prevalence rates for mutans streptococci in children (13,20,27,39).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…mutans and S. sobrinus are the most commonly isolated bacterial species associated with dental caries and are regarded as the main pathogenic microorganisms of the disease (10,11,14,15). The present findings show that the prevalence of mutans streptococci was 94.5% in subjects aged 11-36 years, which is consistent with the findings of a previous study of Down syndrome patients aged 1-48 years (29). However, other studies have reported lower prevalence rates for mutans streptococci in children (13,20,27,39).…”
Section: Discussionsupporting
confidence: 92%
“…To further investigate the association between these pathogens and dental caries, quantification of bacterial proportions is essential. However, few longitudinal studies have examined the relation between these pathogens and caries incidence in general populations (25,27), and even fewer have investigated individuals with ID (28,29). Detection of these organisms is essential for dental caries prediction and subsequent treatment (22).…”
Section: Introductionmentioning
confidence: 99%
“…The S. mutans ’ results corroborate the findings of previous studies 7,11,18 . However, other studies have reported similar 9 or higher counts 17 .…”
Section: Discussionsupporting
confidence: 90%
“…However, the relationship between oral streptococci and dental caries in children with DS is not well characterized. While some studies have shown that the occurrence of dental caries is associated with S. mutans counts in children and adolescents with DS 2,9,20,28 , other authors have not found such association 7 . Thus, investigations to clarify the ecologies of the oral cavities of individuals with DS are necessary 7 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation